Image-guided lung metastasis ablation: a literature review. (1st October 2019) - Prud'homme, Clara; Deschamps, Frederic; Moulin, Benjamin; Hakime, Antoine; Al-Ahmar, Marc; Moalla, Salma; Roux, Charles; Teriitehau, Christophe; de Baere, Thierry; Tselikas, Lambros
Abstract: Purpose: To review the available options of percutaneous ablation of lung metastasis. Methods: General indications, prognostic factors, and image guidance of percutaneous lung ablations were reviewed. Specificities, technical aspects, advantages and limitations of each technic were highlighted. Complications and follow up where also reviewed. Results: Image-guided, percutaneous ablation is of interest for patients with a limit number (<3–5) small metastases (<2–3 cm). Other predictive factors have been reported such as the disease-free interval, the primary tumor, or the proximity with large vessels or bronchus. Radiofrequency ablation (RFA) is the most reported technic, with local control rate >90% for small tumors, and a very low complication rate. Microwave (MWA) and cryoablation are alternative technics developed in the last 15 years to overcome RFA limitations, with encouraging results. Larger ablations zones and less heat sink effect have been described with MWA. On the other hand, cryoablation allows painless treatments under conscious sedation and/or local anesthesia, high accessibility of difficult locations and promising results on prospective multicenter series. Although irreversible electroporation (IRE) could be used for lesions close to main blood vessels as it is not limited by the heat sink effect and does not have significant effects on connective tissue, allowing to treat lesions near to vital organs, preliminary results for lung metastasis are disappointing. Conclusion: Percutaneous ablation of lung metastases, whatever technic is used, is feasible, with high local control rate, and acceptable complication rate. Although indications seem clear enough, validation through controlled trials is mandatory.